(untitled) (Journal of Philosophy Culture and Political Science, 2026)
This article analyzes the events of “Kandy Qantar” through the prism of the concept of hybrid warfare. The bloody events of January 2022 in Kazakhstan continue to provoke controversy and ambiguous assessments not only within the country but also in foreign academic circles. Some question the influence of external forces, others reject the presence of terrorist groups, and still others deny that there was an attempt to change the government, explaining the protests as the ruling elite’s inability to solve the socio-economic problems of society in a timely manner due to corruption, using terrorism as a cover. One thing is clear: the highest value for the state and its citizens is, above all, ensuring political stability and the ability to resolve any conflicts peacefully. Using situational analysis, the authors conducted a comprehensive study of the impact of forms and methods of hybrid warfare aimed primarily at destabilizing the country. Its main elements are informational and ideological narratives that motivate the population to protest with the aim of destabilizing the country. The organized actions of criminal groups, the coordination of protests and the seizure of administrative buildings in different regions of Kazakhstan, and the availability of weapons show that the crisis goes beyond spontaneous social protest and expressions of discontent. The study showed that to prevent threats to national security and ensure political stability in the state, it is necessary to ensure control over the main institutions and resources of state and society management, including information, security, and military resources. Kazakhstan successfully coped with this crisis. Moreover, this crisis opened new prospects for large-scale political reforms in the country to eliminate the excesses of the authoritarian regime. Keywords: political stability, security, modern political process, protests, globalization, hybrid wars, Kazakhstan, "Kandy Kantar".